PENGARUH KUALITAS SISTEM INFORMASI, PERCEIVED USEFULNESS, DAN USER COMPETENCY TERHADAP KEPUASAN PENGGUNA SISTEM INFORMASI AKUNTANSI (Studi Empiris terhadap Bank BTN di Semarang) - Dona Elsafira Anastasya; Abdul Rohman (Diponegoro Journal of Accounting, 2021)
This research’s aims to examine the effect of the satisfaction level of using accounting information systems for evaluating technology that has been applied in a company. The main focus in influencing the satisfaction of using the accounting information system in this study is the quality of the information system, perceived usefulness and user competency. The populations used in this study were all employees of  PT Bank BTN (Persero) Tbk in the city of Semarang. Sampling in this study using the convenience sampling method, which has obtained data samples of 62 respondents from 1 (one) branch office, 8 (eight) sub-branch offices and 3 (three) Bank BTN cash offices in Semarang City. The use of convenience sampling method was chosen because of the ease in obtaining research samples.The research hypothesis testing uses multiple regression analysis, which shows that the quality of information systems has a significant positive effect on satisfaction with the use of accounting information systems, as well as a positive and significant effect of perceived usefulness on satisfaction in using accounting information systems. In addition, user competency has a positive but insignificant effect on satisfaction with the use of accounting information systems.